A phylogenetic perspective on the association between ants (Hymenoptera: Formicidae) and black yeasts (Ascomycota: Chaetothyriales). Issue 1850 (15th March 2017) - Vasse, Marie; Voglmayr, Hermann; Mayer, Veronika; Gueidan, Cécile; Nepel, Maximilian; Moreno, Leandro; de Hoog, Sybren; Selosse, Marc-André; McKey, Doyle; Blatrix, Rumsaïs
Abstract : The frequency and the geographical extent of symbiotic associations between ants and fungi of the order Chaetothyriales have been highlighted only recently. Using a phylogenetic approach based on seven molecular markers, we showed that ant-associated Chaetothyriales are scattered through the phylogeny of this order. There was no clustering according to geographical origin or to the taxonomy of the ant host. However, strains tended to be clustered according to the type of association with ants: strains from ant-made carton and strains from plant cavities occupied by ants ('domatia') rarely clustered together. Defining molecular operational taxonomic units (MOTUs) with an internal transcribed spacer sequence similarity cut-off of 99% revealed that a single MOTU could be composed of strains collected from various ant species and from several continents. Some ant-associated MOTUs also contained strains isolated from habitats other than ant-associated structures. Altogether, our results suggest that the degree of specialization of the interactions between ants and their fungal partners is highly variable. A better knowledge of the ecology of these interactions and a more comprehensive sampling of the fungal order are needed to elucidate the evolutionary history of mutualistic symbioses between ants and Chaetothyriales.